An Overview of the Vine Mealybug (Planococcus ficus) in South African Vineyards and the Use of Entomopathogenic Nematodes as Potential Biocontrol Agent - le Vieux, P.D.; Malan, A.P. (South African Journal of Enology and Viticulture, 2016)
The vine mealybug, Planococcus ficus (Hemiptera: Pseudococcidae), which is the dominant mealybug species in South Africa, is a severe wine and table grape pest and disease vector. Their increasing resistance to chemical pesticides and cryptic lifestyles have led to the search for new control methods. Entomopathogenic nematodes (EPNs) belonging to the families Heterorhabditidae and Steinernematidae are deadly insect pathogens. This paper gives valuable background information on P. ficus and EPNs, while paying particular attention to the potential use of South African EPN species as biocontrol agents against P. ficus.